2011
DOI: 10.1111/j.1551-2916.2011.04416.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Second Harmonic Generation of Lithium Niobium Silicate Glass Ceramics

Abstract: An extended study of lithium niobium silicate glass crystallization with the molar composition 35Li2O–25Nb2O5–40SiO2 is presented. Depending on the heat treatments, both surface and/or bulk crystallizations of the LiNbO3 crystalline phase were observed. X‐ray diffraction together with second harmonic generation (SHG) measurements have revealed a net preferred orientation of the ferroelectric crystallites at the surface which is quite different in the bulk. A striking and promising SHG response estimated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(75 reference statements)
1
17
0
2
Order By: Relevance
“…The one of the region adjacent to the focal point is around 750°C. Both of these T plateaus are in the crystal growth region [23]. Therefore, the large size of crystals can be induced directly by fs laser irradiation when the applied pulse energy is higher than 1 μJ, and this is consistent with the EBSD images in Fig.…”
Section: Discussion: Formation Mechanism Of Fs-laser-induced Orientedsupporting
confidence: 63%
See 1 more Smart Citation
“…The one of the region adjacent to the focal point is around 750°C. Both of these T plateaus are in the crystal growth region [23]. Therefore, the large size of crystals can be induced directly by fs laser irradiation when the applied pulse energy is higher than 1 μJ, and this is consistent with the EBSD images in Fig.…”
Section: Discussion: Formation Mechanism Of Fs-laser-induced Orientedsupporting
confidence: 63%
“…Starting from Yang et al's proposal that PFT acts in ponderomotive force, creating a plasma density gradient, we underline that a space charge is created [27] that is stored in the glass and remains after the pulse has vanished, at least until the next pulse. The high temperature (580°C) [23] is not high enough for erasing the space charge in a few microseconds. Then, as in Yang et al's expression of the heat current, the space charge is asymmetric and its direction is defined by combination of laser polarization and PFT with similar characteristics.…”
Section: Discussion: Formation Mechanism Of Fs-laser-induced Orientedmentioning
confidence: 99%
“…Achieving these polymer materials with high SHG response requires a right balance between the SHG effi ciency and transparency of the materials. [ 46 ] The increase in NPs concentration leads to an enhancement of the generated SH intensity. However, as is mentioned above, it also leads to a decrease in the overall polymer transparency and an increase of the diffuse scattering.…”
Section: Supporting Informationmentioning
confidence: 99%
“…During thermal treatment, such compositions are crystallized by combining the surface and volume mechanisms, with precipitation of the LiNbO 3 crystallites which are very different in size. The analysis of SHG response indicated that the volume crystallization mechanism is desirable since it enables the precipitation of the LiNbO 3 crystals of uniform size [12].…”
Section: Introductionmentioning
confidence: 99%